2013
DOI: 10.1109/lsp.2013.2279269
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Shape-Based Averaging With Neighborhood Prior Model for Multiple Atlas Fusion-Based Medical Image Segmentation

Abstract: Abstract-In medical imaging, merging automated segmentations obtained from multiple atlases has become a standard practice for improving the accuracy. In this letter, we propose two new fusion methods: "Global Weighted Shape-Based Averaging" (GWSBA) and "Local Weighted Shape-Based Averaging" (LWSBA). These methods extend the well known Shape-Based Averaging (SBA) by additionally incorporating the similarity information between the reference (i.e., atlas) images and the target image to be segmented. We also pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…We have shown that MAF strategy significantly improves TV-based fetal brain reconstruction (improvement of 7.03dB with 99% confidence interval for the PSNR). Future work will investigate more advanced fusion strategies such as local weighted voting combined with MRF-based edge-preserving smoothing 22,23 . Also, the atlas selection could be improved by selecting e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that MAF strategy significantly improves TV-based fetal brain reconstruction (improvement of 7.03dB with 99% confidence interval for the PSNR). Future work will investigate more advanced fusion strategies such as local weighted voting combined with MRF-based edge-preserving smoothing 22,23 . Also, the atlas selection could be improved by selecting e.g.…”
Section: Discussionmentioning
confidence: 99%
“…19,22,23 In our framework, we adopt a global weighted voting (GWV) MAF strategy. It is formulated as the following voxel-wise maximization problem:…”
Section: Multi-atlas Fusion (Maf) Strategymentioning
confidence: 99%
“…An alternative approach involves using the signed distance maps of the original atlas label images (Gholipour et al, 2012; Gorthi et al, 2013; Sabuncu et al, 2010; Sjöberg and Ahnesjö, 2013; Weisenfeld and Warfield, 2011a; Xu et al, 2014b). Each label has an associated signed distance map, which takes positive values within the corresponding structure, negative values outside, and the magnitude is proportional to the closest distance to the label boundary.…”
Section: Survey Of Methodological Developmentsmentioning
confidence: 99%
“…In medical image fusion, merging automated segmentations obtained from multiple sources has become a common practice for improving accuracy [13]. Subrahmanyam Gorthi et al proposed two fusion methods -Global weighted shape based averaging and Local weighted shape based averaging.…”
Section: Different Image Fusion Techniquesmentioning
confidence: 99%